Structural and Thermal Analysis of Disc Plate - Manavalan, S.; Kumar, Hulendra; Kumar, Bharath; Raviteja, M.; Ali, Israfil (International Journal of Psychosocial Rehabilitation, 2019)
Braking is a process which converts the kinetic energy of the vehicle into mechanical energy which must be dissipated in the form of heat. The disc brake is a device for de-accelerating or stopping the rotation of a wheel. A brake disc (or rotor) usually made of cast iron or ceramic composites, is connected to the wheel and/or the axle. Friction material in the form of brake pads (mounted on a device called a brake caliper) is forced mechanically, hydraulically, pneumatically or electromagnetically against both sides of the disc to stop the wheel. The disc brake is a device used for slowing or stopping the rotation of the vehicle. Number of times using the brake for vehicle leads to heat generation during braking event, such that disc brake undergoes breakage due to high Temperature. Disc brake model is done by Solidworks and analysis is done by using ANSYS workbench. The main purpose of this project is to study the Thermal analysis of the Materials for the Rene 41, Elgiloy and 6063 T5 Alloy. A comparison between the four materials for the Thermal values and material properties obtained from the Thermal analysis low thermal gradient material is preferred. The results have been compared for better justification. Thus, the results provide better understanding on the thermal characteristic of disc brake rotor and assist the automotive industry in developing optimum and effective disc brake